2006
DOI: 10.1128/jvi.00734-06
|View full text |Cite
|
Sign up to set email alerts
|

PML Contributes to a Cellular Mechanism of Repression of Herpes Simplex Virus Type 1 Infection That Is Inactivated by ICP0

Abstract: Promyelocytic leukemia (PML) nuclear bodies (also known as ND10) are nuclear substructures that contain several proteins, including PML itself, Sp100, and hDaxx. PML has been implicated in many cellular processes, and ND10 are frequently associated with the replicating genomes of DNA viruses. During herpes simplex virus type 1 (HSV-1) infection, the viral regulatory protein ICP0 localizes to ND10 and induces the degradation of PML, thereby disrupting ND10 and dispersing their constituent proteins. ICP0-null mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
416
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 297 publications
(461 citation statements)
references
References 46 publications
43
416
1
1
Order By: Relevance
“…Consequently, PML not only recruits the transcriptional repressor hDaxx to ND10 and thus sites of incoming viral genomes but also itself possesses the ability to suppress HCMV gene expression, although the exact mechanism of PML-mediated silencing remains to be determined. In summary, the results of our study further support the evolving concept that ND10 structures are part of an antiviral defense mechanism of the cell, with individual components of these structures contributing independently to counteract viral gene expression (14,15,43,48,50).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Consequently, PML not only recruits the transcriptional repressor hDaxx to ND10 and thus sites of incoming viral genomes but also itself possesses the ability to suppress HCMV gene expression, although the exact mechanism of PML-mediated silencing remains to be determined. In summary, the results of our study further support the evolving concept that ND10 structures are part of an antiviral defense mechanism of the cell, with individual components of these structures contributing independently to counteract viral gene expression (14,15,43,48,50).…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, plaque formation and IE gene expression of an ICP0-deficient herpes simplex virus type 1 was also shown to be enhanced in PML-negative fibroblasts (15), further supporting the notion of PML and ND10 as mediators of an intrinsic immune defense against herpesvirus infections in general. At the same time, the ND10 constituent hDaxx was identified as a repressor of HCMV IE gene expression and replication (8,45,46,50).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…5 This protein has an E3 ubiquitin ligase activity that induces proteasomic degradation of several cellular proteins, including the promyelocytyc leukemia (PML) protein, and the disruption of PML bodies (also known as ND10), which are involved in repression of gene expression. 5 In the absence of ICP0, PML and PML bodies are preserved, and this correlates with decreased ability to start a lytic infection in human fibroblasts. 5 As amplicons do not express ICP0 or any other immediate-early protein, this inherent antiviral response may also be partially responsible for the silencing observed in some cell types.…”
Section: Herpes Simplex Virus Type 1-based Vectors Al Epsteinmentioning
confidence: 99%
“…5 In the absence of ICP0, PML and PML bodies are preserved, and this correlates with decreased ability to start a lytic infection in human fibroblasts. 5 As amplicons do not express ICP0 or any other immediate-early protein, this inherent antiviral response may also be partially responsible for the silencing observed in some cell types. Perhaps related to this hypothesis, it has been shown that the bacterial DNA sequences present in conventional amplicon vectors cause rapid transgene silencing by forming inactive chromatin in normal human fibroblasts.…”
Section: Herpes Simplex Virus Type 1-based Vectors Al Epsteinmentioning
confidence: 99%